PERSPECTIVES ON THE SPECIFIC FOOTBALL PARAMETERS OF ROMANIA’S THIRD LEAGUE - Antonescu Andrei Gabriel; Stănescu Monica Iulia; Palade Tudor (Sport şi Societate)
Football is one of the most popular sports nowadays. It is practiced all around the world, in the most different environmental, economic or social conditions. Also, the level of performance of football players is extremely varied. Among them, some are professionals, others are amateurs, and some are on the border between the two categories, being semi-professionals. On the other hand, although they come from such different backgrounds and the activity takes place, sometimes, in opposite contexts, there are also aspects that make the practitioners alike: dedication, passion and involvement in football activity. In our work we set out to observe a totally different world from what "great performance" means -the 3rd Football League from Romania. We videotaped and analyzed several games from the 2023-2024 season and indexed player actions. We categorized theseas positive actions (successful passes, shots on goal, goals, rebounds etc.) or negative actions (unsuccessful passes, lost balls, shots on target, received cards etc.). The obtained data were compared with the results from the international specialized literature. Although the differences are obviously present, there is also the prospect that from the 3rd league in Romania it will be possible to start towards the "great performance".